2022
DOI: 10.1161/jaha.122.027386
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Change of Cardiovascular Health Metrics and Long‐Term Risk of Sudden Cardiac Death: The ARIC Study

Abstract: Background The change of cardiovascular health (CVH) status has been associated with risk of cardiovascular disease. However, no studies have explored the change patterns of CVH in relation to risk of sudden cardiac death (SCD). We aim to examine the link between baseline CVH and change of CVH over time with the risk of SCD. Methods and Results Analyses were conducted in the prospective cohort ARIC (Atherosclerosis Risk in Communities) study, started in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…To reduce CVD morbidity and mortality, the AHA defined 7 components of ideal cardiovascular health in 2010 and updated the ICVHM to 8 components recently, named Life’s Essential 8. The ARIC study defined participants with 0 to 2, 3 to 4, and 5 or more ICVHMs as having poor, intermediate, and ideal cardiovascular health, respectively . It was suggested in multiple studies that these metrics were associated with lower diabetes incidence .…”
Section: Discussionsupporting
confidence: 92%
“…To reduce CVD morbidity and mortality, the AHA defined 7 components of ideal cardiovascular health in 2010 and updated the ICVHM to 8 components recently, named Life’s Essential 8. The ARIC study defined participants with 0 to 2, 3 to 4, and 5 or more ICVHMs as having poor, intermediate, and ideal cardiovascular health, respectively . It was suggested in multiple studies that these metrics were associated with lower diabetes incidence .…”
Section: Discussionsupporting
confidence: 92%
“…The associations between absolute change in CVH score and incident cardiovascular events have also been evaluated in some previous studies, and all the results showed that both per 1 additional ideal metric and per 1-point increase in CVH score were associated with a decreased risk of cardiovascular events[ 9 , 10 , 13 , 14 , 21 ]. Lee et al found that per 1-point increase in the CVH score based on LS7 (total 14 points) was associated with a 21 % decrease in the risk of premature cardiovascular events [10] , and Yang et al showed that per 1 additional ideal metric based on LS7 was associated with a 13 % decrease in the risk of total stroke [13] .…”
Section: Discussionmentioning
confidence: 97%
“…However, limited empirical evidence exists on the association between CVH change and incident cardiovascular events. Most studies have indicated that improvement of CVH from low to moderate/high status is associated with a decreased risk of cardiovascular events, such as sudden cardiac death [14] , stroke [12] , and premature cardiovascular events [10] . Compared with the consistent low group, Gaye et al showed that the risk of CVD was statistically decreased in the low to moderate/high group [20] , whereas van Sloten et al found that the risk of CVD was not significantly changed in the low to moderate and low to high groups [9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportional hazards assumption was checked by plotting the log (−log [survival]) versus log (survival time) and by using Schoenfeld residuals. 21 , 23 No evidence was suggestive of potential violation for any exposure‐outcome associations.…”
Section: Methodsmentioning
confidence: 99%